Ways of implementation in the educational activity of the National academy of the National Guard of Ukraine experience of modern local war - Golubok М. G.; Likhodiy О. V.; Nesterenko О. О.; Falko S. А. (Honor and Law, 2019)
The problems of implementation of the experience of modern local wars in the educational activity of the National Academy of the National Guard of Ukraine are considered. Proposals for improving the quality of teaching "Tactics" in the field of knowledge "Military Science" were introduced by introducing the experience of the antiterrorist operation in the East of Ukraine and the local wars of the second half of the 20th - the beginning of the 21st century into the training process of the National Academy of the National Guard of Ukraine. through a system of binary occupations. The variant of use of binary lessons in organization of tactical training of cadets of the National Academy of National Guard of Ukraine, trained on the specialty "Military management" is offered.